Determining Quality Factors Contributing to Chalet and Resort Guest Lodging Satisfaction using SERVQUAL Dimension Analysis - OMAR, Muhd Khaizer; AZMAN, Nur Arnie Sazerin Shamsul; JUSOH, Rosnani; ZAKARIA, Anis; KANG, Enio Kang Sufian (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020, 2020)
The aim of this study is to determine the relationship between quality factors: service, facility, and location and chalet and resort guest satisfaction by utilizing the SERVQUAL dimension. The sample of the study involving 152 guests from five selected chalets and resorts along the beach of Pengkalan Balak , Malacca, Malaysia. The correlation analysis provided supports for the existent of the relationship between guest satisfaction and the studied dimensions. It is noteworthy to justify that customers were satisfied with the service provided and the relationship between the SERVQUAL dimension and satisfaction was explored. Now, the direction of the tourism industry in Malaysia has discerned towards. Thus, the government can sally forth to face the proactive action to support the small and medium industry (SME) tourism business entities by improving the aforementioned quality factors. If the quality is maintained and continued to serve well, the chalet and resort lodging businesses in Pengkalan Balak could have beneficial effects upon the tourism industry which ultimately flourish the surrounding community and spark interest among tourists to visit the destination.